Pengaruh Lingkungan Kerja, Motivasi, Dan Disiplin Kerja Terhadap Kepuasan Kerja Guru SMK Negeri 3 Balikpapan - Nurhasanah, Nurhasanah; Ariani, Misna; Yuliani, Tutik (MEDIA RISET EKONOMI [MR.EKO], 2024)
The purpose of this study was to determine the effect of Work Environmet, Motivation, and Work Discipline on Job Satisfaction of Teachers Vocational High School 3 Balikpapan. The sampling technique in this study was purposive sampling with a sample 68 teachers Vocational High School 3 Balikpapan. Methods of data collection is done by distributing questionnaires. This study uses SmartPLS in processing data. The results of this study indicate that the work environment variable has no significant effect on teacher job satisfaction Vocational High School 3 Balikpapan. Motivation variable has a significant effect on teacher job satisfaction Vocational High School 3 Balikpapan. And work discipline variable has a significant effect on teacher job satisfaction Vocational High School 3 Balikpapan. Keywords: Work Environment; Motivation; Work Discipline; Job Satisfaction.